Pengaruh Net Progit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Food And Beverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - 2021 - Jennifer Sihombing; Kristi Endah Ndilosa Ginting; Michelle Nikholaas Sihombing; Vitri Ayu Telaumbanua; Kevin Thio; Mella Yunita (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research is to examine how stock prices are impacted by Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The information used in this research came from the industrial companies' annual published financial reports for the 2019–2021 period that were listed on the IDX. Using a total sample of 26 Food and Beverage companies, the sampling method is used. The statistical test with multiple regression method and the previously tried F and T tests for hypotheses are the analysis techniques that were used. According to the findings, for the years 2019 through 2021, NPM, ROA, and ROE all had a sizable impact on stock prices in industrial companies on the IDX. NPM does not significantly affect stock prices, at least not in a major way. Stock prices are unaffected by the ROA variable in a major way. Stock values are significantly negatively impacted by the ROE variable. According to this study's results, the coefficient of determination (R2) is equal to 0.310, which indicates that 31% of the Stock Price variable can be explained by the independent variables NPM, ROA, and ROE, while the remaining 69% is explained by other factors outside the equation. Keywords : NPM, ROA, ROE, and Stock Price